2018
DOI: 10.1002/oby.22265
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry Versus Imaging for Prediction of Inflammation Among Hispanic Girls

Abstract: Objective To compare total and regional estimates of body composition, by direct and indirect techniques, for the optimal prediction of CRP among young (9–12 year old), Hispanic girls ( N =232). Methods Standard anthropometric techniques were used to measure height, weight, and waist circumference. Dual energy X-ray absorptiometry (DXA) and peripheral quantitative computed tomography (pQCT) assessed body composition. Fasting serum CRP was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Several studies have found that obesity induces production of pro-inflammatory molecules, promoting a low-level chronic inflammatory state [54][55][56][57], whose relation with aging has also been documented [58,59]. To assess this potential interaction, we conducted stratified analyses using these factors.…”
Section: Plos Onementioning
confidence: 99%
“…Several studies have found that obesity induces production of pro-inflammatory molecules, promoting a low-level chronic inflammatory state [54][55][56][57], whose relation with aging has also been documented [58,59]. To assess this potential interaction, we conducted stratified analyses using these factors.…”
Section: Plos Onementioning
confidence: 99%